Arabidopsis UBC13 differentially regulates two programmed cell death pathways in responses to pathogen and low‐temperature stress. Issue 2 (15th September 2018) - Wang, Lipu; Wen, Rui; Wang, Jinghe; Xiang, Daoquan; Wang, Qian; Zang, Yuepeng; Wang, Zheng; Huang, Shuai; Li, Xin; Datla, Raju; Fobert, Pierre R.; Wang, Hong; et al.
Summary: UBC13 is required for Lys63‐linked polyubiquitination and innate immune responses in mammals, but its functions in plant immunity remain to be defined. Here we used genetic and pathological methods to evaluate roles of Arabidopsis UBC13 in response to pathogens and environmental stresses. Loss of UBC13 failed to activate the expression of numerous cold‐responsive genes and resulted in hypersensitivity to low‐temperature stress, indicating that UBC13 is involved in plant response to low‐temperature stress. Furthermore, the ubc13 mutant displayed low‐temperature‐induced and salicylic acid‐dependent lesion mimic phenotypes. Unlike typical lesion mimic mutants, ubc13 did not enhance disease resistance against virulent bacterial and fungal pathogens, but diminished hypersensitive response and compromised effector‐triggered immunity against avirulent bacterial pathogens. UBC13 differently regulates two types of programmed cell death in response to low temperature and pathogen. The lesion mimic phenotype in the ubc13 mutant is partially dependent on SNC1 . UBC13 interacts with an F‐box protein CPR1 that regulates the homeostasis of SNC1. However, the SNC1 protein level was not altered in the ubc13 mutant, implying that UBC13 is not involved in CPR1‐regulated SNC1 protein degradation. Taken together, our results revealed that UBC13 is a key regulator in plant response to low temperature and pathogens.